Effect of Quencher, Geometry, and Light Outcoupling on the Determination of Exciton Diffusion Length in Nonfullerene Acceptors. Issue 8 (9th January 2022) - Belova, Valentina; Perevedentsev, Aleksandr; Gorenflot, Julien; De Castro, Catherine S. P.; Casademont-Viñas, Miquel; Paleti, Sri H. K.; Karuthedath, Safakath; Baran, Derya; Laquai, Frédéric; Campoy-Quiles, Mariano
Abstract : The correct determination of the exciton diffusion length ( L D ) in novel organic photovoltaics (OPV) materials is an important, albeit challenging, task required to understand these systems. Herein, a high‐throughput approach to probe L D in nonfullerene acceptors (NFAs) is reported, that builds upon the conventional photoluminescence (PL) surface quenching method using NFA layers with a graded thickness variation in combination with spectroscopic PL mapping. The method is explored for two archetypal NFAs, namely, ITIC and IT‐4F, using PEDOT:PSS and the donor polymer PM6 as two distinct and practically relevant quencher materials. Interestingly, conventional analysis of quenching efficiency as a function of acceptor layer thickness results in a threefold difference in L D values depending on the specific quencher. This discrepancy can be reconciled by accounting for the differences in light in‐ and outcoupling efficiency for different multilayer architectures. In particular, it is shown that the analysis of glass/acceptor/PM6 structures results in a major overestimation of L D, whereas glass/acceptor/PEDOT:PSS structures give no significant contribution to outcoupling, yielding L D values of 6−12 and 8−18 nm for ITIC and IT‐4F, respectively. Hence, practical guidelines for quencher choice, sample geometries, and analysis approach for the accurate assessment of L D are provided. Abstract : The modulation effect of light in‐ and outcoupling on the photoluminescence from layered structures of widely employed organic photovoltaics materials, used for the assessment of the exciton diffusion length L D, is investigated. The effect is shown to depend on the optical constants of the layers and the sample architecture. A possible correction method is introduced.